Folwark i stacja królewska w Brodni koło Sieradza - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
The paper discusses results of archaeological investigations conducted at Brodnia, Pęczniew commune, Sieradz province, in 1987, and financed by the Conservator of Monuments for the Province of Sieradz. The investigations are part of a broader research project the object of which is to study remains of late medieval and modern residential and defensive features of the Sieradz region. The village of Brodnia, located at the ford across the river Warta, at the road leading from Sieradz to Kalisz, has for long attracted historians because of the visits of King Władysław Jagiełło who in the years 1401-1435 stayed there 19 times and who held there courts of justice in curia, the highest court in Polar d where the verdicts were brought in by the King himself. The minutes of the court sessions held at Brodnia in 1404-1409 have survived, and the last king to visit the village was Casimir Jagiełło. Brodnia was first mentioned in written records in 1298. For the whole time it was a royal property and was part of the Sieradz district (starostwo) and later of the Szadek tenure. In the western part of the village, on the high bank of the Warta valley there was a farm complex, on the margin of which an earthen mound, over 3 m high, its base measuring 25 m in diamater and its truncated top, 9 m, has survived. In the earlier literature the mound was interpreted as a relic of a fortified residential feature. The object of the investigations was to study the stratigraphy of the mound and to establish its chronology as well as to determine the beginnings of the farm complex.